BBC's Documentary "Stadiums of Hate" and Manufacturing of the News: Case Study in Moral Panics and Media Manipulation. (December 2020) - Rek-Woźniak, Magdalena; Woźniak, Wojciech
The article is based on a critical case study of the BBC's investigative documentary titled Stadiums of Hate and the public's response to it. The documentary was broadcasted 11 days before the kickoff of Euro 2012 (UEFA [Union of European Football Associations] European Championships in Football), the first sport mega event hosted in Poland and Ukraine. The main theme was football-related racism and violence allegedly threatening the safety of the fans coming to the tournament. The article follows Amanda Rohloff's proposal combining the Eliasian conceptual framework of civilizing processes with the moral panics approach to describe the effort to amplify the spiral of public outcry toward the hosts of Euro 2012 in an attempt to modernize and civilize the Eastern European world of football. The moral panics spiral was brought to an end by the tournament which did not justify grim predictions. The article combines analysis of media content and the public statements with interviews conducted with some of the informants of the BBC journalists.